Impact of Fiscal Indiscipline on External Debt in Sub Saharan Africa - Talent Kondo; Victoria Masere; Pretty Moyo (Journal of Governance and Accountability Studies, 2026)
Purpose: This study examines the impact of fiscal indiscipline on external debt in SSA. Methodology: A panel analysis using a Random Effect Model with data spanning September 2009 to December 2020 was employed. Results: The Results from the Random Effects Model (REM) indicate that the primary fiscal balance has a negative impact on external debt. This implies that a primary fiscal deficit raises external debt, whereas a primary fiscal surplus reduces external debt. Conclusions: In estimating the impact of fiscal indiscipline on external debt, this study observed that primary fiscal balances significantly and negatively affect external debt; that is, the lower the primary fiscal balance to a deficit, the larger the external debt accumulated. The study concludes that fiscal indiscipline affects external debt in SSA. Limitations: The study's scope was limited to periods with available data, acknowledging the potential impact of data quality on these findings. Contributions: This study guides policymakers and governments of SSA countries by providing possible ways to maintain a balance between government revenues and expenditures. Novelty: This study offers actionable recommendations for policymakers in Sub-Saharan Africa, emphasizing the need for balanced government revenues and expenditures to promote economic stability. Focusing on sub-Saharan Africa addresses a significant gap in the literature and sets the foundation for future research on effective economic strategies in developing countries. Overall, the findings of this study are essential for enhancing fiscal policies and promoting economic resilience in the region.